New PWM inverter control based on optimal pulse pattern computation without phases symmetry constraints. (March 2023) - Bourgeade, Adrien; Ghanes, Malek; Jean-Pierre, Barbot; Abdelkader, Bouarfa; Maurice, Fadel; Robert, Boisliveau
Abstract: The control of inverters has degrees of freedom that open the way to improve the output harmonic spectrum. Numerous works dealing with this objective have been proposed in the literature, particularly within the definition of switching angles. Among them, the well-known PWM techniques such as Quarter Wave Symmetry (QWS), Half Wave Symmetry (HWS), and Full Wave Symmetry (FWS) are based on Optimal Pulse Patterns (OPP) computation using symmetries angles constraints. In this paper to improve the harmonic quality, the symmetry angles constraints are not considered leading to a new OPP method: Phases Symmetry Relaxation (PSR). To highlight the interest in the proposed PSR method, an evaluation in terms of Weighted Total Harmonic Distortion (WTHD) is performed. Simulation and experimental tests are conducted in comparison with the well known FWS, highlighting the interest in the proposed PSR strategy. Highlights: Optimal pulse pattern pulse width modulation. Phase symmetry relaxation. Voltage source two levels inverter. Optimization based on Sequential quadratic programming. Weighted Total Harmonic distortion.